Interés privado y produccíon actual de conocimiento en ciencia,tecnología e innovación - Héctor Eduardo Cardona Carmona (Trilogía Ciencia Tecnología Sociedad, 2010)
It is a fact that during the last few years, remarkable changes in the production and the appropriation of the knowledge in the global context have been occurring. Based on this fact, this article intends to defend the thesis on that the financing, production and appropriation of the scientific and technological knowledge in the contemporaneous society have become practices that show an increasing tendency of the privatization. This tendency has introduced a new conception, in which interests oriented to the merchandising, commercialization and competitiveness of the knowledge predominate.